Kimilsungism-Kimjongilism and Marxism-Leninism - Pateman, Joe (Politics, religion & ideology, 2021)
In the mid 1970s, the North Korean regime stopped presenting its governing ideology as the creative application of Marxism-Leninism. Since Kim Jong-Un took office, the Workers’ Party of Korea has endorsed Kimilsungism-Kimjongilism, an ideology based upon the theories of Kim Il-Sung and Kim Jong-Il. English language Commentators have long emphasized the differences between North Korean and Marxist-Leninist political theory. Kimilsungism-Kimjongilism has further emphasized these differences. It claims to have established an original political theory. This article challenges that claim. By comparing the two ideologies, it argues that Kimilsungism-Kimjongilism has inherited several political principles from Marxism-Leninism, including a commitment to working class emancipation and the core principles of socialist construction. Although Kimilsungism-Kimjongilism claims to have introduced original socialist principles, these are not that unique. Even North Korea's distinctive Songun (Military First) politics has inherited a Marxist-Leninist rationale. These political similarities illuminate both ideologies. They also expose some inconvenient truths about Marxism-Leninism.